2007
DOI: 10.1007/s11671-006-9035-3
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of double wall carbon nanotube electrodes

Abstract: Electrochemical properties of double wall carbon nanotubes (DWNT) were assessed and compared to their single wall (SWNT) counterparts. The double and single wall carbon nanotube materials were characterized by Raman spectroscopy, scanning and transmission electron microscopy and electrochemistry. The electrochemical behavior of DWNT film electrodes was characterized by using cyclic voltammetry of ferricyanide and NADH. It is shown that while both DWNT and SWNT were significantly functionalized with oxygen cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 27 publications
2
57
0
1
Order By: Relevance
“…It is worth commenting that these multi-walled systems bring the advantage of mixing semiconducting (S) and metallic species (M), which extends the range of applications of DWNTs and TWNTs [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Moreover, the effectiveness of this mixing is directly related to the van der Waals forces mediating the interlayer interactions.…”
Section: Double-and Triple-walled Carbon Nanotubesmentioning
confidence: 99%
“…It is worth commenting that these multi-walled systems bring the advantage of mixing semiconducting (S) and metallic species (M), which extends the range of applications of DWNTs and TWNTs [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. Moreover, the effectiveness of this mixing is directly related to the van der Waals forces mediating the interlayer interactions.…”
Section: Double-and Triple-walled Carbon Nanotubesmentioning
confidence: 99%
“…The capacitance properties of these systems depend on the number of graphene walls (single-, double-, or multi-wall), the nature of the electrode material, the composition of the electrolyte solution, and the structure of the carbon nanotube layer. The specific capacitance of pristine CNTs is relatively low and ranges from 2 to 45 F g À1 for SWCNTs [35][36][37][38][39][40][41][42] and 3 to 80 F g À1 for MWCNTs [36][37][38][42][43][44]. The capacitance properties of thin films of CNTs are collected in Table 1.…”
Section: Capacitance Properties Of Single-and Multi-walled Carbon Nanmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] It has been shown that NAD + , which is a product of the electrochemical oxidation of NADH, passivates carbon nanotube-and edge plane pyrolytic graphite-based electrodes to a significantly less extent than it does to the surfaces of glassy carbon or metallic electrodes. [2][3][4][13][14][15] Little is known about the mechanism of the passivation of electrodes. The mechanism of adsorption of NADH/NAD + on glassy carbon and mercury electrodes was studied by cyclic voltammetry.…”
Section: Introductionmentioning
confidence: 99%